Enantioselective Hydrogenation of Ethyl Pyruvate With Cinchonidine Modified Pt/SiO2 and PtSn/SiO2 Catalysts - Ibañez, María Fernanda (2003)
The enantioselective hydrogenation of ethyl pyruvate on Pt/SiO2 catalysts modified with a chiral compound, cinchonidine, and promoted with tin was studied in this work. The enantioselectivity of the nonpromoted Pt/SiO2 catalysts depends strongly on the particle size; when the particle size is larger, the enantiomeric excess obtained is higher. The addition of small tin amounts (Sn/Pt 001) produces a slight increase in the initial hydrogenation rate, and at the same time, a relative small change in the ee% value, but larger tin amounts generate a decrease in the initial hydrogenation rate together with a marked diminution of the ee value.